An Abstraction Theory in Marketing: Examining the Relationship between the Effectiveness of Art and Heritage Marketing Dimensions and Customer Value - Essam, Reem (Archives of Business Research, 2022)
This research is attempting to find a new realm contributing to the current marketing practices through proposing a new method of marketing of art and heritage artefacts. This research tries to find a hint of a new angle through marketing practices on the relationship among abstraction, art and heritage marketing and customer value in art museums, galleries and exhibitions in Egypt. This research aims at gaining insight into the abstract marketing themes for a better use of the best marketing practices at museums, illuminating the way for other researchers to establish additional studies that look deeply into the relationships among abstraction theory, art & heritage dimensions and customer value. This research uses a quantitative research design beside a qualitative exploratory study for a clearer overview of the way art museums; galleries and exhibitions customers in Egypt view the provided service, through the use of an in-depth interview. The research develops and tests a conceptual model through quantitative analysis, using a self-administrated questionnaire of eight hundred copies distributed to art and heritage customers at some different art museums; galleries and exhibitions in greater Cairo and Alexandria. 320 questionnaire copies have been collected through a non-probability snowball sampling and convenience sample technique. The statistical analysis for the data, using SPSS and Path Analysis through AMOS have proved that there are positive correlations among the study variables, proving that abstraction has a significant positive impact on art and heritage marketing dimensions and that art and heritage marketing dimensions have a significant positive impact on customer value.